Impact of Fuel and Energy Complex on Sustainable Development of Mineral Extracting Regions: the World Experience - Barbara, Anna; Sluder, Lyubov (My University, 2019)
The fossil fuel sectors and export of its products occupy a leading position in the economy of many countries and directly affect the sustainability of national economies. Therefore, in the long term an adequate vision of the development of these sectors is of great importance in forecasting and planning the strategic development of these countries. The wide use of coal fuel in the world energy consumption will remain for quite a long time; however, the environmental problems associated with its production are a serious factor hindering the possibility of a transition to the sustainable development of coal-producing regions. There is an obvious need for a balanced approach in developing greater industrial potential while protecting the environment. The world is slowly moving away from coal as other forms of energy have become cheaper and environmental concerns mount. The authors analyzed the world and domestic experience in the initiation, promotion and implementation of projects that contribute to the sustainable development of the leading mining regions of the world. The ability of the authorities to clearly define strategic priorities, improve the business climate, effectively distribute and improve the quality of regional resources and infrastructure creates the prerequisites for enhancing the sustainable competitive advantages of a region, business, and public welfare.